Isolasi Bakteri Pendegradasi Phenanthrene dari Batanta-Salawati Raja Ampat Papua - Riffiani, Rini (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTIsolation of Bacteria Degrading Phenanthrene in Batanta- Salawati Districts Raja AmpatPapua. Polycyclic aromatic hydrocarbons (PAHs) are important environmental contaminantsin soil and water. These compounds have a potential risk to human health, as many of them arecarsinogenic and toxic to marine organisms such as diatome, gasthrophode, mussel, and fish.Phenanthrene is one of the hazardous hydrocarbon compounds. The purpose of this researchwas to characterize microbial strains from Batanta-Salawati Raja Ampat Papua Island and theirability to remove phenanthrene. Two isolates were identified at their physiological characteristicsbased on salinity tolerance, pH tolerance and the composition of nitrogen base. Molecularidentification based on 16S rRNA gene sequences indicated that bacteria had the highestsimilarity with Rhodobacteraceae bacterium F9 and Roseobacter sp. RW 37.Rhodobacteraceae bacterium F9 could grow optimum on ONR7a media with 5% salinity andat pH of 5-7,5 while Roseobacter sp. RW 37 could grow optimum on ONR7a media with 2%salinity and at pH of 6,2-7,5.Key words: Phenanthrene, physiological characteristic, molecular identification, Raja Ampat